2020
DOI: 10.1063/5.0016341
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and inter-conduction band optical absorption processes in β -Ga2O3

Abstract: β-Ga2O3 is an ultra-wide bandgap semiconductor and is thus expected to be optically transparent to light of sub-bandgap wavelengths well into the ultraviolet. Contrary to this expectation, it is found here that free electrons in n-doped β-Ga2O3 absorb light from the IR to the UV wavelength range via intra- and inter-conduction band optical transitions. Intra-conduction band absorption occurs via an indirect optical phonon mediated process with 1/ω3 dependence in the visible to near-IR wavelength range. This fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The probe wavelength is 800 nm. When the probe is polarized along the a*-axis (perpendicular to the b-and c-axis), the change in transmission is due to optical absorption from photoexcited free electrons (intra-conduction band absorption [30]). As the polarization of the probe is changed away from the a*-axis toward the c-axis, additional absorption due to defects is observed that makes ∆T /T more negative in the first few hundred picoseconds.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The probe wavelength is 800 nm. When the probe is polarized along the a*-axis (perpendicular to the b-and c-axis), the change in transmission is due to optical absorption from photoexcited free electrons (intra-conduction band absorption [30]). As the polarization of the probe is changed away from the a*-axis toward the c-axis, additional absorption due to defects is observed that makes ∆T /T more negative in the first few hundred picoseconds.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Very notably, the shape of the ∆T /T transient is also polarization dependent suggesting that different loss mechanisms are contributing to the probe absorption when the probe is polarized along the c-axis and a*-axis. In recently reported work [30], we have examined the ∆T /T transient for probe polarization along the a*-axis in detail and shown that, for this polarization, the probe experiences optical loss only due to intra-conduction band transitions (a form of free-carrier absorption) characterized by a 1/ω 3 frequency dependence, where ω is the center frequency of the probe pulse. Optical absorption related to defects is not observed for probe polarized along the a*-axis.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a typical defect state absorption. In Singh et al (2020), they did the absorption spectra of different probe wavelengths (515, 600, 660, 800, 940 nm) under 450 nm excitation, and found that they were related to the transition in the conduction band (intraband free-carrier absorption) through α∝ω −3 fitting (Drude model, as shown by the red dotted line in Figure 4), while the extra absorption due to defect state between 500 and 650 nm is ignored. The difference between our experimental results and the Drude line proves the existence of defect state absorption.…”
Section: Bound Electrons-related Nonlinear Optical Parametersmentioning
confidence: 99%
“…The study of gallium oxide nonlinear absorption/refraction dynamics is of great significance to the design of all-optical switches and ultrafast optoelectronic devices. In 2020, Okan Koksal et al verified the intra-and inter-conduction band optical absorption processes of β-Ga 2 O 3 through steady state and ultrafast optical spectroscopy measurements (Singh et al, 2020), but they ignored the influence of defect state at 500-650 nm on absorption, which we will be explained explicitly in this paper. Gallium oxide has many impurities or intrinsic defects, such as Si, Sn, oxygen vacancy and gallium vacancy, which promote the radiative and nonradiative recombination of carriers (Varley et al, 2010;Dong et al, 2017;Neal et al, 2018).…”
Section: Introductionmentioning
confidence: 96%